UJI EFEKTIVITAS SEDIAAN KRIM EKSTRAK ETANOL DAUN AFRIKA (Vernonia amygdalina Del.) TERHADAP BAKTERI Propionibacterium acnes. - Atriana Zain; Maulana, Maulana Zulkarnain Imansyah (Jurnal Kesehatan Yamasi Makassar, 2023)
African leaves (Vernonia amygdalina Del.) or what used to be called "Bitter Leaves" is one of the plant varieties used as herbal medicine. African leaves are efficacious as antibacterial, antifungal, antiallergic, antioxidant, analgesic and anti-inflammatory. African leaves contain secondary metabolites such as flavonoids, saponins, tannins, steroids, terpenoids. This study aims to determine the effectiveness of the preparation of ethanol extract cream of African leaves (Vernonia amygdalina Del.) against Propionibacterium acnes bacteria. This research was conducted using the Laboratory Experimental method. A cream of African leaf ethanol extract (Vernonia amygdalina Del.) was made using a concentration of 5% 10% and 15%. Testing the effectiveness of inhibition against Propionibacterium acnes using the paper disk diffusion method. Based on the research results, the ethanol extract cream of African leaves (Vernonia amygdalina Del.) was able to inhibit the growth of Propionibacterium acnes. Concentration of 15% got the largest average inhibition zone compared to other concentrations, namely 17.77 mm, 10% concentration got an average result of 15.78 mm and 5% concentration got an average inhibition zone of 13.53 mm while the positive control has the largest inhibition zone, which is 21.73 mm.